The design Process of a Reading Comprehension Manual (2015)
ABSTRACT: Material design is an important part in the teaching practices. This article describes the process of material design of a foreign language (FL) reading manual for undergraduate students at Universidad de Antioquia (Medellín, Colombia). Action research was used as methodological guide to design the manual. Four in-service English teachers participated in the process of the design and they took into account issues such as the program of reading comprehension I, readings that contain cultural information and active background knowledge, reading with visual aids, and exercises that involved pre-, while-, and post-reading activities. As a result, a sample of a reading strategy is given in order to illustrate how teachers worked and designed the manual. Conclusions suggest that the process of designing a manual helped teachers understand their beliefs and practice in teaching reading in a foreign language.